Effects of SO2 on selective catalytic reduction of NO with NH3 over a TiO2 photocatalyst. Issue 2 (10th March 2015) - Yamamoto, Akira; Teramura, Kentaro; Hosokawa, Saburo; Tanaka, Tsunehiro
Abstract: The effect of SO2 gas was investigated on the activity of the photo-assisted selective catalytic reduction of nitrogen monoxide (NO) with ammonia (NH3 ) over a TiO2 photocatalyst in the presence of excess oxygen (photo-SCR). The introduction of SO2 (300 ppm) greatly decreased the activity of the photo-SCR at 373 K. The increment of the reaction temperature enhanced the resistance to SO2 gas, and at 553 K the conversion of NO was stable for at least 300 min of the reaction. X-ray diffraction, FTIR spectroscopy, thermogravimetry and differential thermal analysis, x-ray photoelectron spectroscopy (XPS), elemental analysis and N2 adsorption measurement revealed that the ammonium sulfate species were generated after the reaction. There was a strong negative correlation between the deposition amount of the ammonium sulfate species and the specific surface area. Based on the above relationship, we concluded that the deposition of the ammonium sulfate species decreased the specific surface area by plugging the pore structure of the catalyst, and the decrease of the specific surface area resulted in the deactivation of the catalyst.